Dysfunction of Smartphone Use on Mental Health of Undergraduates in Lagos State, Nigeria - Biobaku, Muftau Olanrewaju; Adisa, Abayomi Bamidele (European Scientific Journal, ESJ, 2026)
Smartphone use has significant impacts on the mental health of youth, especially undergraduates, who perceive it as an integral part of their identity and social lives. Previous studies have examined the effects of smartphones globally, with limited attention given to undergraduates in Lagos State. This study investigates the correlation between smartphone use and mental health indicators among undergraduates in Lagos State, identifying the prevalent mental health issues associated with its use. Anchored on the Problematic Internet Use Model, the study employed a survey research method. The population comprised undergraduates from six universities (three public and three private). A total of 630 undergraduates aged 20–40 were selected using disproportionate sampling. Data were collected using two standardized instruments: the Smartphone Addiction Scale (SAS) and the Depression Anxiety Stress Scale. Descriptive statistics and correlation analysis were applied. Results revealed that 76.8% of respondents were female, and 58.4% spent more than six hours daily on their smartphones. The prevalent mental health issues identified were smartphone addiction, stress, anxiety, depression, sleep deprivation, and social alienation. There was a significant association between smartphone usage and mental health issues (χ² = 164.633 > critical value = 9.488, df = 4, p < 0.05). Smartphone usage significantly influenced the well-being of undergraduates (χ² = 372.438 > critical value = 9.488, df = 4, p < 0.05). Excessive smartphone use was predictive of mental health issues, manifesting as addiction, stress, and anxiety.